Visões do paraíso: as expedições de Francisco de Orelhana e Pedro Teixeira na Amazônia - Pedro Freitas Jardim de Mattos (Navigator)
This work have with objective the analises of two expeditions for the Amazon Rainforest. The first expedition has been promoted by Francisco de Orelhana in 1542 and the second expedition by Pedro Teixeira in 1639. Based in this two expeditions we want confirm or not, the thesis of Sérgio Buarque de Hollanda in “Raízes do Brasil” and “Visão do Paraíso”, where he defended a major pragmatism for part of the portuguese, in contrast with one fantastic spanish imaginary.